STRATEGI KEPALA MADRASAH DALAM MENGAPLIKASIKAN VISI DAN MISI MTSN 5 TABALONG - Miranti Miranti (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2023)
A good strategy from the principal in applying the vision and mission is highly expected, in order to improve the quality of the school. Therefore it is necessary to formulate long-term and short-term programs in achieving its goals. Based on this statement, the formulation of the problem in this study is how was the strategy carried out by the head of the madrasah in applying the Vision and Mission at MTsN 5 Tabalong?, and what are the long and short term goals and programs that have been carried out by the Head of MTsN 5 Tabalong?. The goal to be achieved is to find out the achievement of the strategy carried out by the head of the madrasa in applying the Vision and Mission at MTsN 5 Tabalong and the long and short term goals and programs that have been carried out by the Head of MTsN 5 Tabalong. This type of research is field research and the approach taken is a qualitative approach. The object of this research is the strategy carried out by the madrasa head in applying the vision and mission at MTsN 5 Tabalong and the subjects of this research are the head of MTsN 5 Tabalong and 3 teachers at MTsN 5 Tabalong. The data collection techniques are carried out by means of interviews, observation and documentaries. Data processing techniques using data reduction, data display and data verification and data analysis using descriptive qualitative. The results of this study indicate that the madrasa head's strategy in applying the vision and mission at MTsN 5 Tabalong is illustrated in the following description: 1) The achievement of the strategy carried out by the madrasah head in applying the vision and mission is by using several strategies in achieving the existing vision and mission and apply the vision and mission by determining and assigning madrasah residents according to their respective fields. The head of MTsN 5 Tabalong is also always active in all activities at the madrasa and is even the first person in protecting his citizens, because he not only governs, but is also directly involved in it. 2) The long-term goal is to make MTsN 5 Tabalong the leading MTsN in Tabalong Regency in 2030. The short-term program is achieved within 1 to 5 years and this is illustrated by the existing vision and mission. While the programs that have been implemented include participating in competitions at the district and provincial levels and even at the national level, involving teachers in teacher training, and having extra curriculars fostered by competent people